Chitosan-based agronanochemicals as a sustainable alternative in crop protection - Maluin, Farhatun Najat; Hussein, Mohd Zobir (MDPI, 2020)
The rise in the World’s food demand in line with the increase of the global population has resulted in calls for more research on the production of sustainable food and sustainable agriculture. A natural biopolymer, chitosan, coupled with nanotechnology could offer a sustainable alternative to the use of conventional agrochemicals towards a safer agriculture industry. Here, we review the potential of chitosan-based agronanochemicals as a sustainable alternative in crop protection against pests, diseases as well as plant growth promoters. Such effort offers better alternatives: (1) the existing agricultural active ingredients can be encapsulated into chitosan nanocarriers for the formation of potent biocides against plant pathogens and pests; (2) the controlled release properties and high bioavailability of the nanoformulations help in minimizing the wastage and leaching of the agrochemicals’ active ingredients; (3) the small size, in the nanometer regime, enhances the penetration on the plant cell wall and cuticle, which in turn increases the argochemical uptake; (4) the encapsulation of agrochemicals in chitosan nanocarriers shields the toxic effect of the free agrochemicals on the plant, cells and DNA, thus, minimizing the negative impacts of agrochemical active ingredients on human health and environmental wellness. In addition, this article also briefly reviews the mechanism of action of chitosan against pathogens and the elicitations of plant immunity and defense response activities of chitosan-treated plants.